Neuroprotective coordination of cell mitophagy by the ATPase Inhibitory Factor 1. (January 2016) - Matic, Ivana; Cocco, Stefania; Ferraina, Caterina; Martin-Jimenez, Rebeca; Florenzano, Fulvio; Crosby, James; Lupi, Ramona; Amadoro, Giusy; Russell, Claire; Pignataro, Giuseppe; Annunziato, Lucio; Abramov, Andrey Y.; et al.
Graphical abstract: Neurons adapt to hypoxia-reoxygenation stress by upregulating the F1 FoATPase inhibitor factor 1 (IF1 ) which facilitates PARK2 dependent mitophagy and prevents detrimental ATP depletion. This is important to aid ri-equlibration of homeostatic respirations in neurons and avoid ischemia cell death. Abstract: The mitochondrial ATPase Inhibitory Factor 1 (hereafter referred to as IF1 ) blocks the reversal of the F1 Fo -ATPsynthase to prevent detrimental consumption of cellular ATP and associated demise. Herein, we infer further its molecular physiology by assessing its protective function in neurons during conditions of challenged homeostatic respiration. By adopting in vitro and in vivo protocols of hypoxia/ischemia and re-oxygenation, we show that a shift in the IF1 :F1 Fo -ATPsynthase expression ratio occurs in neurons. This increased IF1 level is essential to induce accumulation of the PTEN-induced putative kinase 1 (PINK-1) and recruitment of the mitophagic ubiquitin ligase PARK-2 to promote autophagic "control" of the mitochondrial population. In IF1 overexpressing neurons ATP depletion is reduced during hypoxia/ischemia and the mitochondrial membrane potential (Δ Y m ) resilient to re-oxygenation as well as resistant to electrogenic, Ca 2+ dependent depolarization. These data suggest that in mammalian neurons mitochondria adapt to respiratory stress by upregulating IF1, which exerts a protective role by coordinating pro-survival cell mitophagy and bioenergetics resilience.